Classificação Internacional de Funcionalidade e Burn Specific Health Scale " Brief - Brasil em pacientes com queimadura - Passos, Maria Claudia Nehme [UNIFESP] (2018)
Introduction: Analyzing the decrease in mortality and the increase of survival rate in patients with burn, it is important to consider the quality of life and functioning. The results of this important outcomes take impact in the lives of people who have been burned. Objective: To evaluate the difference between International Classification of Functioning (ICF) and Burn Specific Health Scale-Brief-Brazil (BSHS-B-Br) in patients with burn injury. Method: Eighty patients with burns who underwent ambulatory follow-up were evaluated. The BSHS-B-Br was used for quality of life. A data collection sheet based on the ICF was used for functioning. The Spearman Correlation Coefficient test was used for analysis. Results: BSHS-B-Br presented an average of 127.12 (SD ± 23.03). The correlation between the total score of BSHS-B-Br with the CIF for body functions was moderated (r = -0.5307; p <0.001), for body structures it was weak (r = - 0.4787; p < 0.001), for the activities and participation it was also weak (r = 0.4385, p <0.001) and for the environment it was moderated (r = -0.5027, p <0.001). Conclusion: There was a correlation between the ICF results obtained from the patient's perspective and the BSHS-B-Br for this population evaluated, demonstrating that the use of this classification can be incorporated in the examination of patients. Furthermore, it can be a practical instrument for the different decision measures in the attention to this population.